2015
DOI: 10.1002/icd.1954
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation in At‐Risk Preschoolers: Longitudinal Associations and Influences of Maternal Histories of Risk

Abstract: Emotion regulation is a key challenge of early childhood. The present study examined emotion regulation behaviour longitudinally from infancy to preschool. The continuity of emotion regulation was explored within the larger ecological context of maternal childhood histories of aggression and social withdrawal and maternal use of constructive and non-constructive behaviours. Forty-five mothers with childhood histories of aggression or social withdrawal from the Concordia Longitudinal Risk Project, a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Eleven studies were included in the meta-analysis of parent-focused strategies in the first year of life [ 14 , 35 , 37 , 38 , 40 , 50 , 51 , 52 , 53 , 54 , 55 ], providing 1809 participants. The weighted mean effect size was r = 0.00, CI 95% [−0.17, 0.17], indicating a lack of a relationship overall between distress expression and parent-focused strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies were included in the meta-analysis of parent-focused strategies in the first year of life [ 14 , 35 , 37 , 38 , 40 , 50 , 51 , 52 , 53 , 54 , 55 ], providing 1809 participants. The weighted mean effect size was r = 0.00, CI 95% [−0.17, 0.17], indicating a lack of a relationship overall between distress expression and parent-focused strategies.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Mortensen and Barnett (2019) found a link between intrusive maternal parenting at 14 months and ER capacities during toddlerhood (14–36 months). Furthermore, mothers' use of non‐constructive verbal expression predicted maladaptive ER styles in preschoolers, especially increased child fretting, overactivity, and negative attention‐seeking (August et al, 2017). Saritaş et al (2013) also confirmed that maternal harsh parenting, including hostility and rejection, was associated with lower ER in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Grady and Callan (2019) found that parent ET behaviors (measured using a similar picture book reading task as the present study) such as explaining emotions were effective in helping shy toddlers with low dispositional self-regulation regulate their fear and socially engage with an unfamiliar experimenter. On the contrary, parents’ use of negative, nonconstructive language in emotional situations was associated with preschoolers’ reduced use of adaptive emotion-regulation strategies (August et al, 2017). In conjunction, these findings suggest that not only parent ET is linked to children’s arousal and regulatory capacities, but also the type of ET matters.…”
Section: Links Between Parent Et and Children’s Effortful Controlmentioning
confidence: 99%